CGP 35348, GABAB Receptor Antagonist, Has a Potential to Improve Neuromuscular Coordination and Spatial Learning in Albino Mouse following Neonatal Brain Damage. (6th April 2014) - Gillani, Q.; Ali, M.; Iqbal, F.
Abstract : To study the effect of CGP 35348 on learning and memory in albino mice following hypoxia ischemia insult, 10 days old albino mice were subjected to right common carotid artery ligation followed by 8% hypoxia for 25 minutes. Following brain damage, mice were fed on normal rodent diet till they were 13 week old. At this time point, mice were divided into two groups. Group 1 received saline and group 2 intrapertoneally CGP 35348 (1 mg/mL solvent/Kg body weight) for 12 days. A battery of tests used to assess long term neurofunction (Morris water maze, Rota rod and open field) along with brain infarct measurement. Overall CGP 35348 has improved the motor function in male and female albino mice but effects were more pronounced in female albino mice. In open field, CGP 35348 treated female albino mice had demonstrated poor exploratory behavior. During Morris water maze test, gender specific effects were observed as CGP 35348 had improved spatial learning and memory and swimming speed in male albino mice but had no effect in female albino mice following hypoxia ischemia encephalopathy (HIE). We concluded that GABAB receptor antagonists CGP 35348 can be used to improve gender based spatial memory.